Regulatory Factors Creating Waqf Bank the Third Sector Organizations : A Case Study in Indonesia - Muhamad Fauzi; Rahmat Dahlan; Iwan Agustiawan Fuad (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2024)
The development of waqf in Muslim countries has grown positively, contributing to socio-economics. Waqf, as one of the instruments of innovation, increases awareness of its value and widespread use. Banking functions as a profit institution centred on the financial sector by collecting and distributing funds to the public for the benefit of national development. The utilisation of the Banking and Waqf sectors is literally the opposite, but has great innovation for the long-term public interest. This phenomenon has given rise to civil organisations as third-sector organisations concerned with integrating the principles and benefits of the banking and waqf sectors. Unfortunately, developing countries in Indonesia, with a Muslim majority population, have high levels of generosity and religiosity, but literacy and inclusion of waqf are still low. The purpose of the study is to determine the regulatory factors that support the creation of waqf banks as third-sector organisations in Indonesia. The study uses a qualitative method with a systematic literature review. Data collection uses secondary data from international journals indexed by Scopus and SINTA published between 2011 and 2023 with the keywords "waqf bank regulation". Data analysis uses a systematic literature review (SLR). The study found that the regulation to create a waqf bank as a third sector organisation in Indonesia requires strengthening of waqf bank education, total government support, large contributions from waqf institutions of third sector organisations, the fundamental role of Islamic banking in waqf banks and services that extend without limits to waqf banks. The study implies that the better the regulation to create a waqf bank in Indonesia, the better the role of third-sector organisations in supporting regulation and education to the public.